The Influence of Herringbone Technique and Reading Interest towards Students’ Reading Comprehension Achievement of the Eleventh Grade Studentsof SMAN 2 Palembang - Trisseda Angraini; Tahrun Tahrun; Mulyadi Mulyadi (ELTE Journal (English Languange Teaching and Education), 2018)
AbstractThis study was to investigate the influence of herringbone technique and reading interest towards reading comprehension achievement of the eleventh grade students of SMA N 2 Palembang. The population of this study was all the eleventh grade students of SMA N 2 Palembang. The sample was 72 students were taken by using two-stage random sampling; cluster random sampling and simple random sampling technique. In carrying out the research, the writer used an experimental method; factorial design.The writer distributed pre-test, post-test, and reading interst questionnaire in collecting the data. Then, in analyzing the data, the writer used t-test and two-way ANOVA. The result of this study analysis that; first, there was significant difference in reading comprehension achievement between students who had high reading intrest taught by using herringbone technique. Second, there was significant difference in readingcomprehension achievement between students who had low reading intrest taught by using herringbone technique. Third, there was significant difference in reading comprehension achievement between students who had high reading interest and those who had low reading interest taught by using herringbone technique. Fourth,there was significant difference in reading comprehension achievement between students who had high reading interest and those who had low reading interest taught by using traditional teaching. And the last, there was significant interaction effect ofherringbone technique and reading interest on reading comprehension achievement of the eleventh grade students of SMA N 2 Palembang.Keywords: Herringbone technique, Students’ Reading Interest, Reading Comprehension Achievement.